(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
For allocation color signs it is necessary to define their referential sphere. Principles of semantic compatibility of nominatives of color with nouns at level of classes and separate lexemes are investigated in article.